Review of graphene modulators from the low to the high figure of merits. (3rd April 2020) - Liu, Jiamin; Khan, Zia Ullah; Wang, Cong; Zhang, Han; Sarjoghian, Siamak
Abstract: In this paper, the basic physics of modulator are discussed and traditional silicon modulator in the early years is involved as a comparison. Fifty-seven research articles about graphene modulators are reviewed in detail. All the figure of merits including modulation depth, modulation speed, footprint, modulation bandwidth, operation bandwidth, and insertion loss of these modulators are well studied. The challenges and problems for graphene modulators are addressed by analyzing the first twenty-five references while the last thirty-five references of graphene modulators are reviewed to address the higher figure of merits that are still developing. Physics of other 2D materials are also mentioned as a comparison, especially a modulator by black phosphorus. We believe this review will give a good roadmap to develop better graphene modulators that solves the challenges and problems in this field.